Tuntutan Kerja Sebagai Faktor Dominan Mempengaruhi Loyalitas Karyawan dan Kepuasan Kerja pada Karyawan Toko Emas di Pasar Tradisional Kabupaten Grobogan - Pingkan Ananda Ardiyanto; Masitha Fahmi Wardhani; Artha Febriana; Ana Kadarningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the influence of work integrity and job demands on employee loyalty, with job satisfaction as a mediating variable on gold shop employees in traditional markets in nine sub-districts in Grobogan Regency. The method used is explanatory quantitative research with PLS-SEM analysis using SmartPLS version 4.1.1.6, involving 154 respondents selected through purposive sampling technique. The results of the study indicate that work integrity does not significantly influence job satisfaction or employee loyalty. In contrast, job demands have a significant positive effect on job satisfaction and loyalty, although the direction of the influence is different from the initial hypothesis. In addition, job satisfaction has a significant positive effect on employee loyalty, and is proven to mediate the relationship between job demands and loyalty, but does not mediate the relationship between work integrity and loyalty. These findings confirm that employee loyalty is more influenced by perceptions of job demands and levels of job satisfaction than by work integrity. Practically, the results of the study recommend the importance of proportional management of job demands and increasing aspects of job satisfaction to strengthen employee loyalty in gold shops.